1994
DOI: 10.1177/036354659402200204
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Ossification of the Shoulder: The Bennett Lesion

Abstract: We report a series of ossific lesions of the posterior inferior glenoid in a group of elite baseball players. We hope to clarify the etiology, diagnosis, and treatment of the Bennett lesion. From August 1985 to August 1991, we identified six professional baseball pitchers and one college pitcher with evidence of ossification of the shoulder on plain radiographs, computed tomography, or magnetic resonance imaging. Arthroscopic examination was performed in all cases. All seven players had identifiable posterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(61 citation statements)
references
References 18 publications
1
58
0
2
Order By: Relevance
“…Thus, while Bennett proposed that overgrowth of the posteroinferior glenoid represented an osteophytic extension of the glenoid rim itself, Ferrari et al suggested that the calcific changes in the region may instead be due to repetitive traction of the posterior capsule and PIGHL during the extremes of the throwing motion. 27 Other studies have supported these findings as well. 48,60 Greater tuberosity changes are also commonly found on the radiographs of internal impingement patients.…”
Section: Radiographic Findingsmentioning
confidence: 74%
See 1 more Smart Citation
“…Thus, while Bennett proposed that overgrowth of the posteroinferior glenoid represented an osteophytic extension of the glenoid rim itself, Ferrari et al suggested that the calcific changes in the region may instead be due to repetitive traction of the posterior capsule and PIGHL during the extremes of the throwing motion. 27 Other studies have supported these findings as well. 48,60 Greater tuberosity changes are also commonly found on the radiographs of internal impingement patients.…”
Section: Radiographic Findingsmentioning
confidence: 74%
“…6 Most subsequent reports have refuted the association between the triceps and the bony exostosis lesion or Bennett lesion, as it is most commonly called. 27, 54 Bennett also described articular-sided fraying of a superficially intact supraspinatus tendon as a typical finding, but he thought that it was related to anterior shoulder pain and not glenoid impingement. 6 In 1992, Walch et al 80 published a landmark article in which 30 athletes were assessed for shoulder pain.…”
Section: Internal Impingement Of the Shouldermentioning
confidence: 99%
“…Several hypotheses have been proposed regarding the mechanisms of this lesion, such as traction on the posterior joint capsule or triceps tendon during the follow-through phase of throwing, posterior impingement of the humeral head on the glenoid in the late-cocking phase, or a wringing action during the acceleration phase. [1][2][3]6,7 In addition, local irritation of the joint capsule and axillary nerve by the bony spur and internal impingement have been suggested as possible causes for how the bony spur induces posterior shoulder pain in throwing. [6][7][8] The pathologic significance of the Bennett lesion is still controversial, and which type of Bennett lesion induces throwing pain is not clear.…”
mentioning
confidence: 99%
“…Vários desses autores atribuem ao desequilíbrio de forças entre os grupos musculares, que controlam os movimentos do ombro. Dentre as diferentes fases de movimentos executados acima da cabeça no arremesso, existem duas que são críticas para o aumento da dor no ombro: a fase de preparação para o arremesso ("cocking") e a fase final de desaceleração ("follow-through"), que são descritas por FERRARRI (1994) 10 . A associação de movimentos repetitivos acima da cabeça e erros de treinamento referentes ao gesto esportivo do lançamento, provocam o aparecimento de sintomas e, supostamente, provocam também as acomodações tissulares adaptativas que acarretam a instabilidade glenoumeral.…”
Section: Discussionunclassified